A Case of Myeloid Sarcoma following Allogeneic HSCT Presenting as Localized Hip Pain - Shannon Zhang; Casey Charlton; Akshay Amaraneni; Keri Maher (Case Reports in Hematology)
Myeloid sarcoma is a rare variant of acute myeloid leukemia (AML) which presents as an extramedullary soft tissue mass. Due to the rarity of this disease, along with nonspecific presenting symptoms, diagnosis can be delayed or missed without a high index of suspicion. In this case, we discuss a patient diagnosed with AML relapse in the form of myeloid sarcoma two years after allogeneic hematopoietic stem cell transplant (alloHSCT) for myelodysplastic syndrome (MDS) with the initial presentation for back pain misdiagnosed as spinal stenosis. This case report aims to help healthcare providers in recognizing the early signs and symptoms of this disorder as well as provide information in regards to treatment options and risk assessment.